SOCIAL CAPITAL AS PLANNING HUMAN RESOURCES IN EFFORTS TO IMPROVE THE QUALITY OF ISLAMIC EDUCATION INSTITUTIONS - Ahmad Bachtiar Firdaus; Binti Maunah (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2023)
This study aims to analyze social capital as an ingredient in human resource management planning to improve the quality of Islamic education. With superior human resource planning, it is hoped that social capital will be created as a form of actualization of improving the quality of Islamic educational institutions. This study uses a qualitative method. Data collection techniques with a literature review approach. The results of this study found that social capital as a human resource planning material includes values instilled in Islamic educational institutions that must be applied as role models that guide the behavior of educators and education staff, adhered norms can foster integrity, trust (trust) mutual trust and trust, participation in a network of Islamic educational institutions, and proactive action to be able to help contribute to the advancement of Islamic educational institutions.